Case‐only gene–environment interaction between ALAD tagSNPs and occupational lead exposure in prostate cancer. Issue 6 (5th February 2014) - Neslund‐Dudas, Christine; Levin, Albert M.; Rundle, Andrew; Beebe‐Dimmer, Jennifer; Bock, Cathryn H.; Nock, Nora L.; Jankowski, Michelle; Datta, Indrani; Krajenta, Richard; Dou, Q. Ping; Mitra, Bharati; Tang, Deliang; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Black men have historically had higher blood lead levels than white men in the U.S. and have the highest incidence of prostate cancer in the world. Inorganic lead has been classified as a probable human carcinogen. Lead (Pb) inhibits delta‐aminolevulinic acid dehydratase (ALAD), a gene recently implicated in other genitourinary cancers. The ALAD enzyme is involved in the second step of heme biosynthesis and is an endogenous inhibitor of the 26S proteasome, a master system for protein degradation and a current target of cancer therapy. METHODS Using a case‐only study design, we assessed potential gene–environment (G × E) interactions between lifetime occupational Pb exposure and 11 tagSNPs within ALAD in black (N = 260) and white (N = 343) prostate cancer cases. RESULTS Two ALAD tagSNPs in high linkage disequilibrium showed significant interaction with high Pb exposure among black cases (rs818684 interaction odds ratio or IOR = 2.73, 95% CI 1.43–5.22, P = 0.002; rs818689 IOR = 2.20, 95% CI 1.15–4.21, P = 0.017) and an additional tagSNP, rs2761016, showed G × E interaction with low Pb exposure (IOR = 2.08, 95% CI 1.13–3.84, P = 0.019). Further, the variant allele of rs818684 was associated with a higher Gleason grade in those with high Pb exposure among both blacks (OR 3.96, 95% CI 1.01–15.46, P = 0.048) and whites (OR 2.95, 95% CI 1.18–7.39, P = 0.020). CONCLUSIONS Genetic variation in ALAD may modify associations between Pb and prostate cancer. Additional studies of ALAD, Pb, and prostate cancer are warranted and should include black men. Prostate 74:637–646, 2014. © 2014 Wiley Periodicals, Inc.